“Transfer of Knowledge from English Writing Classes to Writing in the Discipline” - HAMANI, Nasrine (Journal of Human Sciences, 2015)
The present study investigates the rates of correlation between the module of written expression and three other ones namely: Linguistics, Literature, and Culture. The study is based on an analysis of the students’ exam marks obtained in the aforementioned modules at the University of Constantine 1, Department of English Letters and Languages. It seeks to determine whether students transfer the writing rules from one discipline to another, and how far these writing conventions are reflected in their compositions.  The remote objective of such a study will be the adaptation of the appropriate approach leading to a successful transfer of the writing rules across the disciplines.